2013
DOI: 10.1080/13803395.2013.844770
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diagnosis threat on academic self-efficacy in mild traumatic brain injury

Abstract: The current study examined the effect of diagnosis threat on self-efficacy and neuropsychological performance in mild traumatic brain injury (TBI). Forty-nine participants with a history of mild TBI were randomized to a diagnosis threat or control group. The diagnosis threat group were told they were selected based on their history of TBI, while control group participants were told to perform their best. Individuals in the diagnosis threat group reported significantly lower academic self-efficacy than control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Bayesian analysis was used so that we could incorporate previous knowledge about the effects of diagnosis threat on cognition in mTBI (Blaine et al, 2013; Carter-Allison et al, 2016; Kinkela, 2008; Kit et al, 2014; Ozen & Fernandes, 2011; Suhr & Gunstad, 2002, 2005; Trontel et al, 2013) with the current results, through the use of priors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bayesian analysis was used so that we could incorporate previous knowledge about the effects of diagnosis threat on cognition in mTBI (Blaine et al, 2013; Carter-Allison et al, 2016; Kinkela, 2008; Kit et al, 2014; Ozen & Fernandes, 2011; Suhr & Gunstad, 2002, 2005; Trontel et al, 2013) with the current results, through the use of priors.…”
Section: Methodsmentioning
confidence: 99%
“…Our prior estimate of the effect of diagnosis threat on cognition in those with a history of mTBI was obtained by performing a meta-analysis of the studies mentioned above (Blaine et al, 2013; Carter-Allison et al, 2016; Kinkela, 2008; Kit et al, 2014; Ozen & Fernandes, 2011; Suhr & Gunstad, 2002, 2005; Trontel et al, 2013). We used all available cognitive performance data, as reported by the original authors, and used a multivariate regression model with random effects (Konstantopoulos, 2011) to account for the nesting inherent in the data (level 1: test variables; level 2: tests; level 3: studies; level 4: research laboratories).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…43 In this context, the fact that our participants generally did well on several laboratory measures of executive functioning, despite rating themselves poorly on the BRIEF-A, is consistent with previous findings in the literature that suggested that diagnosis threat affects primarily perceived self-efficacy and not necessarily actual cognitive test performance. 44 Neither the self-ratings nor the informant ratings correlated with the results from the WCST or TOL. This was consistent with hypothesis 4.…”
Section: Informant Ratings Of Executive Functioning After Mild Tbimentioning
confidence: 97%
“…That the effect is subtle becomes all the more obvious when looking at the weighted effect sizes for each of the cognitive and self-reported domains of functioning: all were small, with the exception of one domain (i.e., intellectual ability). Importantly, intellectual ability was assessed in only two out of six studies Trontel et al, 2013) and to our knowledge there is no compelling existing rationale why diagnosis threat -or the label of MHI -would particularly affect this domain. Our supplementary analysis, which incorporated the findings of two alternative samples, also provided only modest support for the idea that labels such as MHI have serious detrimental effects.…”
Section: Discussionmentioning
confidence: 99%